Cyber Religion as a Digital Learning Alternative: Perceptions and Practices of Islamic Studies Students at Muhammadiyah University of Surabaya - Nugraha, Adam Satria; Huda, Sholihul; Anam, Khoirul; Syarifuddin, Angga Pratama; Hidayah, Taufik (Ta'allum: Jurnal Pendidikan Islam, 2025)
Purpose – This study aims to explore how students at the Faculty of Islamic Studies, Muhammadiyah University of Surabaya, utilize cyber religion as an alternative source of Islamic learning in the digital era. It investigates their preferred platforms, motivations, types of content consumed, engagement patterns, and perceptions of online religious authority. Methods – Employing a qualitative case study approach, the research collected data through non-participatory observation, in-depth interviews with 15 students, and document analysis of digital artifacts. Thematic analysis was used to identify patterns across the data, supported by triangulation to ensure validity. Findings – The results indicate that students actively use platforms such as YouTube, TikTok, and Islamic websites for religious learning. Their engagement is driven by both academic and personal motives, with fiqh and aqidah being the most frequently accessed topics. Students demonstrate selective trust in digital preachers, forming hybrid models of religious authority. While cyber religion enhances religious understanding, it also raises concerns about information credibility and theological consistency. Research implications – The study highlights the need for Islamic higher education institutions to integrate digital literacy into their curricula, enabling students to critically evaluate online religious content. It also suggests a reevaluation of how authority and authenticity are framed in contemporary Islamic learning environments. Value – This research contributes a localized, empirical analysis of cyber religion among university students in Indonesia. It bridges theoretical concepts of digital religion with real-world student practices, offering insights into the transformation of religious learning in a digitally connected society.